Fulminant Pseudomembranous Colitis Presenting as Sigmoid Stricture and Severe Polyposis with Clinical Response to Intracolonic Vancomycin - Sai Wah Cheung; Kin Kong Li (Case Reports in Medicine)
Clostridium difficile infection (CDI) is the most common cause of antibiotic-associated diarrhea. Severe diseases carry significant morbidities such as septic shock, acute kidney injury, bowel perforation, and mortality. Immunocompromising conditions increase the risk of developing the disease but whether these individuals suffer a more fulminant course or warrant a more potent first-line treatment is still controversial issue. Hereby we report a case of a cirrhotic patient with life-threatening pseudomembranous colitis complicated by colonic stricture, initially refractory to standard treatment but with subsequent improvement on intracolonic vancomycin.